A Corpus-assisted Discourse Analysis of ‘The Star Online’ Columns - Ismail, Habibah (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Languages used by journalists is often characterised by the writers’ personal point of view. This is especially true for columnists whose writings are based on their subjective opinions, usually published in a series (McNair, 2008). Consequently, it is important for columnists to create and maintain relationships with the target audience and in so doing, columnists use the power of language to communicate and interact with their readers. Not only are readers engaged when they respond to columns with their comments, other forms of feedback are now provided such as options to click the ‘like’ button or from a scale of ‘emojis’, usually at the end of the article –increasing the challenge for writers to produce a good piece of writing. According to McNair (2008, p109), this is not only entertaining for the reader, the thought “that we will disagree with a columnist whose opinions occupy the other end of the ideological spectrum from our own is often what compels us to read”. However, journalistic commentary may require critical review as we are aware of the influence and how changes in the media environment are impacting its demand and supply (Višňovský & Radošinská, 2017).